Participatory outcomes, quality of life and barriers faced by stroke survivors in the rural Eastern Free State - Cook, Petri Johan (Stellenbosch : Stellenbosch University, 2017)
Thesis (MHumanRehabSt)--Stellenbosch University, 2016.